Cyclical and welfare effects of public sector unions in a Real-Business-Cycle model - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Motivated by the highly-unionized public sectors, the high public shares in total employment, and the public sector wage premia observed in Europe, this paper examines the importance of public sector unions for macroeconomic theory. The model gen- erates cyclical behavior in hours and wages that is consistent with data behavior in an economy with highly-unionized public sector, namely Germany during the period 1970-2007. The union model is a significant improvement over a model with exogenous public employment. In addition, endogenously-determined public wage and hours add to the distortionary effect of contractionary tax reforms by generating greater tax rate changes, thus producing significantly higher welfare losses.
Keywords: C68; E62; J45; J51; 330; fiscal policy; public employment; public wages; public sector unions